Experimental Study of Demonstration Exercise Models on the Performance of Tennis Field Service Biomechanics: Studi Eksperimen Model Latihan Demonstration Terhadap Performa Biomekanika Service Tenis Lapangan - Maqbulatullah, Bilqis; Hidayatullah, M. Furqon; Purnama, Sapta Kunta (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of the interaction between training models on the performance of tennis service biomechanics. This study used an experimental method with a 2 x 2 factorial design. The population in this study were all 12 players of the male KKO SMPN 1 Surakarta. The sampling technique used is saturated sampling, the size of the sample taken is 12 players. The data analysis technique in this study used ANOVA. Based on the results of the study, it turns out that players who have high eye-hand coordination with the live demonstration exercise model have a tennis service biomechanics performance of 189,356 better than players with high eye-hand coordination and receive treatment with a video demonstration exercise model of 28,815. Players who have low eye-hand coordination with the video demonstration exercise model have a tennis service biomechanics performance of 76,701 better than players with low eye-hand coordination and receive treatment with a live demonstration exercise model of 48,290. So it can be concluded that there is an interaction between the exercise model and eye-hand coordination on the biomechanics performance of tennis service. Players who have high eye-hand coordination are more suitable if given a live demonstration exercise model. Players who have low eye-hand coordination are more suitable if given a video demonstration exercise model.